To which countries do European psychiatric trainees want to move to and why? - KILIÇ, ÖZGE; Pinto da Costa, M.; Giurgiuca, A.; Holmes, K.; Biskup, E.; Mogren, T.; Tomori, S.; Kilic, ÖZGE; Banjac, V.; Molina-Ruiz, R.; Palumbo, C.; Frydecka, D.; et al. (My University, 2017)
Background: There is a shortage of psychiatrists worldwide. Within Europe, psychiatric trainees can move between countries, which increases the problem in some countries and alleviates it in others. However, little is known about the reasons psychiatric trainees move to another country.